99.6k views
0 votes
What is the fully simplified answer to sqrt(7/18) + sqrt(5/8) - sqrt(7/2)

User SimonG
by
5.5k points

1 Answer

3 votes

Answer:


=(-4√(7)+3√(5))/(6√(2))

Explanation:

Given expression as:


=\sqrt{(7)/(18)}+\sqrt{(5)/(8)}-\sqrt{(7)/(2) }

We need to simplify the given expression.

Solution:

We have:


=\sqrt{(7)/(18)}+\sqrt{(5)/(8)}-\sqrt{(7)/(2) }

Rewrite the expression as:


=(√(7))/(3√(2)) - (√(7))/(√(2)) +(√(5))/(2√(2))


(√(7))/(√(2) ) is a common factor to the first two terms.

Using distributive property we can factor out
(√(7))/(√(2) ) from the first two terms.


=(√(7))/(√(2))((1)/(3) -1) +(√(5))/(2√(2))


=(√(7))/(√(2))((1-3)/(3)) +(√(5))/(2√(2))


=(√(7))/(√(2))((-2)/(3)) +(√(5))/(2√(2))


=-(2√(7))/(3√(2)) +(√(5))/(2√(2))


√(2) is common factor, so we can factor
√(2) from the above expression.


=(1)/(√(2) )( -(2√(7))/(3) +(√(5))/(2))


=(1)/(√(2) )( (-2* 2√(7)+3* √(5))/(6))


=(1)/(√(2) )( (-4√(7)+3√(5))/(6))


=(-4√(7)+3√(5))/(6√(2))

Therefore, we get simplified answer as.


=(-4√(7)+3√(5))/(6√(2))

User Moein Hosseini
by
6.2k points